Pegylated Phospholipid Nanomicelles Containing Budesonide Or Beclimethasone Dipropionate For Pulmonary Delivery - Sahib, Mohanad Naji (2011)
The aims of the present study were to formulate and evaluate nanomicelles containing poorly water soluble corticosteroids, budesonide (BUD) or beclomethasone dipropionate (BDP) for pulmonary delivery using PEGylated polymers (PEG5000-DSPE and PEG2000-DSPE). All the sterically stabilized phospholipid nanomicelles (SSMs) were successfully prepared using a co-precipitation and reconstitution method. The SSMs were characterised by different physicochemical methods. There were significant differences between the maximum solubilisation tendencies of PEG5000-DSPE and PEG2000-DSPE for BUD, which were approximately 605.71±6.38 and 646.27±4.93 μg/ml, respectively. The maximum solubilisation tendencies of PEG5000-DSPE and PEG2000-DSPE for BDP were approximately 209.65±7.74 and 210.01±5.28, respectively. These results showed that PEGylated polymers had greater tendencies to solubilise BUD than BDP. The mean particle sizes at maximum solubilisation of BUD:PEG2000-DSPE (15.97±1.91 nm) and BDP:PEG2000-DSPE (15.44±1.66 nm) were smaller than BUD:PEG5000-DSPE (20.45±1.65 nm) and BDP:PEG5000-DSPE (19.99±0.98 nm). Blank SSMs of PEG5000-DSPE were successfully lyophilised at a concentration of about 5 mM, while 10 mM of PEG2000-DSPE was needed for lyophilisation.